Flux and Rejection of Salt Using Membrane - Mamat, Nurul Aznin (Universiti Teknologi Petronas, 2004)
The concept ofseparating liquid mixtures (salt solution) using membrane technology has gained tremendous applications in the industry. This is due to the number ofadvantages possessed by the membrane, such as ease of operations, low energy consumption, easy for expansion, small floor area, cost effectiveness and good weight and space efficiency. The reverse osmosis membranes are specified in terms of their "percentage rejection of salts". The membranes that are supplied are classified as tubular type, which is widely used and have turbulent flow conditions. Liquid permeates through the membrane and feed emerges in a more concentrated form onexit from module. The objectives ofthis research are to investigate the performance ofmembrane in order to determine the flux and rejection salt, also to determine the importance parameters such as concentration at different pressure, permeability of water and percentage of salt remove by using different type of chemicals. The experimental equipment consisted of four RO membranes with same material and in-line system sensor, which allows data acquisition system on a continuous base on pressure, flow rates and also weight of permeates. In the process, retentate is recycled tothe feed tank and permeate is collected separately. From the data obtained and graph plotted, it shows that flux and rejection increased as increasing the pressure but decreased with the concentration. More concentrated the solution will reduce the number of flux and rejection in theROmembrane. Different type of chemicals wasused in order to compare the flux and rejection based on the molecular weight and ionic size. Higher in molecular weight and ionic size shows lower the flux and rejection. Parameters are analysed so that optimum-operating conditions are suggested. In this approach, the activity of the membrane selected is noted and compared with the literature/theoretical results.